Effect of Teaching Life Skills to the Students on Improvement in Overall Schools’ Environment - Haider, Syed Imran; Burfat, Prof. Dr. Fateh Muhammad (IJRDO- Journal of Educational Research, 2017)
Life skills are basic and necessary capacities which enable an individual to participate successfully in social and personal life. Teaching of these skills has been recognized as a successful strategy to address a variety of issues related to children. In Pakistan, unfortunately Life Skills are not an exclusive part of our mainstream curricula of primary and secondary schools. However, different schools in Karachi have taught a specialized life skills education curriculum under an initiative of a civil society organization. This paper is an assessment of if, teaching of Life Skills to the Students effect the Overall Schools’ Environment or not. To assess the effect of life skills teaching on improvement in school environment, teachers, and students of the selected schools in Karachi were selected as study subjects. A total of 10 Focused Group Discussions with students and 05 with teachers were conducted. The results showed that the school environment improved positively and a significant decrease in cases of bullying was observed in addition to improved cleanliness and discipline in the school.